The minor prophets an expositional commentary - Boice, James Montgomery, 1938-2000 (Grand Rapids, MI Kregel, 1996)
Contents: v. 1 : Hosea - Jonah; v. 2 : Micah-Malachi. Includes bibliographical references and indexes.
Two volumes complete in one.
Keywords: Bible. O.T. Minor prophets -- commentaries